Incidencia del narcotráfico en las relaciones de cooperación entre Colombia, Perú y Bolivia - Ibarra Canencio, Ángela María (Pontificia Universidad Javeriana, 2014)
Drugs constitute not only the biggest but one of the principle problems that the condition the relations between the United States and the Andean countries. Colombia, Peru and Bolivia have become the primary centers of production and marketing of the majority of the drugs that arrive to the USA. This caracterization has meant that the Andean countries have become identified with the narcotics problem; the result has been that, in one form or another, many aspects of the bi-lateral relations have been conditioned by this situation.